เบญจมาศ: พัฒนาการทางภาพแทนและบทบาทเชิงสัญลักษณ์ในบริบทวัฒนธรรม: Chrysanthemum: The Evolution of Representation and Symbolic Roles in Cultural Contexts - Li, Chang; ธรรมอินทร์ลาด , อภินันท์ (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
This academic article examines the representations of the chrysanthemum (Also known as ju or chrysanthemum flower) within the context of Chinese culture by tracing its historical development from the Zhou dynasty (pre-Qin period) through the Han and Wei dynasties. Over time, the chrysanthemum gradually crystallized into a symbol of pure and noble virtue, a meaning that is most clearly articulated in the poetry of Tao Yuanming. Literary works from this period played a crucial role in consolidating the symbolic status of the chrysanthemum and establishing its enduring influence on later cultural and literary interpretations. Furthermore, the study reveals that following the era of Tao Yuanming, the representations of the chrysanthemum expanded and branched out into various multidimensional meanings during the Tang and Song dynasties. The representations of the chrysanthemum in classical poetry and ancient writings reveal a wide range of symbolic dimensions. These include its association with the morally upright and dignified gentleman, resilience and endurance in the face of adversity, images of autumnal solitude and melancholy, its role within the cultural practices of the Double Ninth Festival (Chongyang Festival, expressions of nostalgia and longing for one’s homeland, as well as its function as a polysemous cultural symbol. Collectively, these multifaceted representations reflect the dynamic interaction between literary expression and cultural values, illustrating how the chrysanthemum has served as a stable yet adaptable symbol embodying the worldview, ethical ideals, and emotional sensibilities of Chinese society across different historical periods. Keywords: Chrysanthemum imagery, Historical evolution, Polysemous cultural symbolism